Study Design and Participants’ Profile in the Sub-Cohort Study in the Japan Environment and Children’s Study (JECS) - Makiko Sekiyama (Journal of Epidemiology, 2022)
Background: The Japan Environment and Children’s Study (JECS) is a nationwide birth cohort study investigating environmental effects on children’s health and development. A Sub-Cohort Study has begun, conducting extended exposure and outcome measurements by targeting a subgroup randomly selected from the JECS Main Study. We report the Sub-Cohort Study methodology and participants’ baseline profiles. Methods: Of 100,148 children in the JECS Main Study, children born after April 1, 2013 who met eligibility criteria ([1] all questionnaire and medical record data from children and their mothers collected from the first trimester to 6 months of age, [2] biospecimens [except umbilical cord blood] from children and their mothers collected at first to second/third trimester and delivery) were randomly selected for each Regional Centre at regular intervals. Face-to-face assessment of neuropsychiatric development, body measurement, paediatrician’s examination, blood/urine collection for clinical testing and chemical analysis, and home visits (ambient and indoor air measurement and dust collection) are conducted. Participants are followed up at 1.5 and 3 years old for home visits, and 2, 4, 6, and 8 years old for developmental/medical examination. The details of protocols after age 10 are under discussion. Results: Of 10,302 selected children, 5,017 participated. The profiles of the participating mothers, fathers and children did not substantially differ between the Main Study and Sub-Cohort Study. Conclusion: The JECS Sub-Cohort Study offers a platform for investigating associations between environmental exposure and outcomes.